(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Suicide is a serious global public health concern that impacts people everywhere. Every year, it causes close to a million fatalities. Knowing the events that result in a suicidal attempt may help in the development of suicide prevention techniques because a past suicidal attempt is the best indicator of a future suicide. One of the most significant predictors of attempted suicide is psychiatric disease. The study’s objectives were to examine the psychological conditions that contribute to suicide attempts. Methods: The present study was carried out at the Aligarh, Uttar Pradesh-based Jawahar Lal Nehru Medical College and Hospital’s department of psychiatry. Between December 2018 and November 2019, suicide attempters who were sent for mental evaluation from various hospital departments were assessed. A total of 45 patients were examined, and it was discovered that 56.25 percent of them also had psychological disease, leaving the remaining 43.75 percent healthy. The majority of the participants in our study had a diagnosable mental condition. In our study, major depressive disorder was the most frequent contributing factor.